Risco para quê? - a arte urbana e a produção do espaço público na urbe latino-americana - Carolina Maria Soares Lima (2021)
The present master’s dissertation, submitted as a partial requirement to obtain a master's degree in geography to the Graduate Program in Geography of the Federal University of Minas Gerais, receives the title of " Risco para quê? - A arte urbana e a produção do espaço público na urbe latino-americana". The research was carried out between the years of 2020 and 2021. In the text, the author discusses the notions related to the public space in contemporary cities, the concept of representation in geography and the possible links between art, representations and space public nowadays. Following, there are chapters that seek to discuss case analyses in three different urban contexts in Latin America. The first is in Comuna 13, located in the Colombian city of Medellín, where street art, tourism and violence are part of the daily life at the Commune*. The second case is located in the city of São Paulo, on the edge of political conflicts, which says that it respects urban art and the appropriation of public space through manifestations of peripheral culture. Finally, in the third case, through exploratory research, the analysis is placed in Belo Horizonte, as a focus for the works of art of the "Circuito Urbano de Arte" and the reactions of the society and the own State against the works. From the analysis, the relationships that were established between a manifestation of urban culture and its own production of space are verified, having as a central question: How do graffiti, mural, and pixel work relate to (re) social production of space in different urban contexts? Under the hypothesis that urban art reinforces and denounces the social contradictions present in the production and reproduction of urban space, in addition to the bibliographical review, the collection of empirical data was derived through interviews, documentary analysis, focal groups and observations of non-participants. This research opens, furthermore, doors, for questions and details not only in the context of geography but also in other fields of knowledge.